Cardiovascular safety of abiraterone acetate in metastatic castration-resistant prostate cancer patients: a prospective evaluation. (February 2018) - Prati, Veronica; Ruatta, Fiorella; Aversa, Caterina; Gernone, Angela; Galizia, Danilo; Bonzano, Alessandro; Torino, Sofia; Nuzzolese, Imperia; Marandino, Laura; Aglietta, Massimo; Ortega, Cinzia
Aim: The aim of this study is to evaluate cardiotoxicity of abiraterone acetate (AA) in metastatic castration-resistant prostate cancer patients (pts) with cardiovascular comorbidities or coronary artery disease (CAD) risk factors.Patients & methods: We prospectively analyzed pts receiving AA in order to evaluate correlations between cardiotoxicity onset and CAD risk factors or cardiovascular comorbidities.Results: Eighty-seven pts were enrolled, with median treatment duration of 9 months (1–44). At baseline, 84 pts (96%) had CAD risk factors. During treatment four pts (4; 6%) developed hypertension and 26 pts (30%) worsened the preexisting hypertension. Median left ventricular ejection fraction were 64 and 63% at baseline and after treatment, respectively.Conclusion: AA appears to be safe in pts with cardiovascular comorbidities or CAD risk factors.